1994
DOI: 10.1177/009862839402100309
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Students to Read Journal Articles

Abstract: A technique is described that motivates students to complete assigned readings of journal articles. The technique requires students to write a summary and critique of each article on an 8 × 5 in. index card. Students completing the readings receive two types of tangible benefits: extra course credit and use of their notecards during subsequent tests. Objective assessment of the technique in two classes indicated that students turned in notecards for 73.7% of the readings, and only one student failed to submit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Extra credit can be a divisive issue for many academics, but it has been shown to be a motivational force to improve student participation in classroom or course-related activities (Carkenord, 1994;Junn, 1995;Roberts, 2000).…”
Section: The Survey Paradoxmentioning
confidence: 99%
“…Extra credit can be a divisive issue for many academics, but it has been shown to be a motivational force to improve student participation in classroom or course-related activities (Carkenord, 1994;Junn, 1995;Roberts, 2000).…”
Section: The Survey Paradoxmentioning
confidence: 99%
“…Boniecki and Moore (2003) demonstrated that giving credit for comments and questions asked in class increased student participation. Perhaps instructors could use credit points to promote discussion, in the same way instructors have used credit to reward attendance (Thorne, 2000), reading journal articles (Carkenord, 1994), and serving as a research participant (Padilla-Walker, Zamboanga, Thompson, & Schermsal, 2005).…”
Section: Credit For Commentsmentioning
confidence: 99%
“…Multiple strategies have been implemented to increase student reading compliance and course performance, such as completion of out-of-class assignments that require reading (Carkenord, 1994;Ryan, 2006), daily written quizzes (ConnorGreene, 2000), and randomized reading quizzes (Ruscio, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Limited research on the impact of active learning strategies has included the impact on students' reading behaviors (Carkenord, 1994;Connor-Greene, 2000;Morling et al, 2008;Ryan, 2006). I am unaware of any studies that report the impact of quizzing on objective measures of whether, and how thoroughly, students read on a daily basis.…”
Section: Introductionmentioning
confidence: 99%